CCAFS & GRA CLIFF-GRADS Webinar Series (Session 1): Using modeling, life-cycle assessment, and trade-off analysis to understand low emission options - CGIAR Research Program on Climate Change, Agriculture and Food Security; Global Research Alliance on Agricultural Greenhouse Gases (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Agenda What is low emissions development? And is it achievable? - Meryl Richards More rice, less water and less greenhouse gas emissions in Colombia - Abubakar Halilu Girei Optimising environmental efficiency of dairy intensification strategies for delivery of milk and beef in Costa Rica - Ridha Ibidhi Discussion of first two presentations Data requirement to develop higher Tier N2O emissions inventory - Sebastián Vangeli Preliminary experimental results of different water and nutrient management practices for narrowing maize yield gap in Ethiopia - Yohannes Gelan Regassa Discussion of second two presentations Conclusion - Meryl Richards